Human subcutaneous dirofilariasis of forearm an unusual presentation - Parasappa Joteppa Yaranal; M M Priyadarshini; B Purushotham (Wolters Kluwer Medknow Publications, 2015)
Human subcutaneous dirofilariasis (HSD) is a rare zoonotic filarial infection caused by filarial worms of the genus Dirofilaria. In view, recent rise in human Dirofilaria repens infections in several regions of the world, is considered as emerging zoonotic infection transmitted to man by zooanthrophilic blood sucking insects. Most of the documented cases of human dirofilariasis recorded in India are ocular infections and very few cases of subcutaneous dirofilariasis have been reported. We hereby present a case of subcutaneous human dirofilariasis of forearm and also emphasize on increased awareness of this entity for clinicians and pathologists in the differential diagnosis of patients with subcutaneous nodules.